2008
DOI: 10.1002/9780470151808.sc01f07s7
|View full text |Cite
|
Sign up to set email alerts
|

TLX1 (HOX11) Immortalization of Embryonic Stem Cell–Derived and Primary Murine Hematopoietic Progenitors

Abstract: The ability to generate genetically engineered cell lines is of great experimental value. They provide a renewable source of material that may be suitable for biochemical analyses, chromatin immunoprecipitation assays, structure‐function studies, gene function assignment, and transcription factor target gene identification. This unit describes protocols for TLX1 (HOX11)‐mediated immortalization of murine hematopoietic progenitors derived from in vitro differentiated murine embryonic stem cells, or from primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…We and others have reported that enforced expression of TLX1 promotes the immortalization of murine hematopoietic progenitors derived from bone marrow as well as from fetal liver, yolk sac and in vitro differentiated embryonic stem cells from various mouse strains at relatively high frequency (reviewed in Hawley et al, 2008). One caveat of these studies is that gene delivery via MLV-based MSCV retroviral vectors was used to introduce the TLX1 transgene into the target cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have reported that enforced expression of TLX1 promotes the immortalization of murine hematopoietic progenitors derived from bone marrow as well as from fetal liver, yolk sac and in vitro differentiated embryonic stem cells from various mouse strains at relatively high frequency (reviewed in Hawley et al, 2008). One caveat of these studies is that gene delivery via MLV-based MSCV retroviral vectors was used to introduce the TLX1 transgene into the target cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of TLX1 to disrupt normal hematopoietic processes has also been demonstrated in a number of in vitro studies, where retroviral expression of TLX1 promoted the immortalization of murine progenitor cells derived from various hematopoietic sources (Hawley et al, 1994a; Hawley et al, 1997; Keller et al, 1998; Yu et al, 2002; Owens et al, 2003; Yu et al, 2003; reviewed in Hawley et al, 2008). Structure-function analysis of the TLX1 protein showed that an intact homeodomain is necessary for hematopoietic progenitor cell immortalization but regions near the NH 2 and COOH termini of TLX1 are not essential for immortalizing activity (Hawley et al, 1997; Owens et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…(i) Labeling of apo-Tf. We labeled Tf by following the procedure described in references 7 [FBS], 100 U/ml penicillin-streptomycin, 2 mM glutamine, 10 ng/ml interleukin-3 [IL-3], 2 ng/ml IL-6, 5 ng/ml IL-11, 50 ng/ml c-kit ligand) for 5 days (25).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro approaches have also demonstrated the potential of TLX1 to disrupt normal hematopoietic processes and promote the immortalization of murine progenitor cells derived from various hematopoietic sources, including bone marrow, fetal liver, yolk sac and embryonic stem cells [11,17-21] (reviewed in [22]). Several studies have provided evidence that TLX1 induces progenitor immortalization by blocking differentiation while concurrently increasing replicative capacity [23-27].…”
Section: Introductionmentioning
confidence: 99%